Prevalence of oral mucosal lesions in dental patients with tobacco smoking, chewing, and mixed habits: A cross-sectional study in South India - Prashant B Patil; Renuka Bathi; Smitha Chaudhari (Journal of Family and Community Medicine, 2013)
Background: A variety of oral mucosal lesions and conditions are associated with the habit of smoking and chewing tobacco, and many of these carry a potential risk for the development of cancer. There have been no studies that report the prevalence of habits and associated oral changes in the population in Dharwad region, of Karnataka, south India. Materials and Methods: A hospital-based, cross-sectional study was carried out at SDM Dental College (Dharwad, Karnataka). A total of 2400 subjects (1200 subjects with and 1200 subjects without habits) attending the dental hospital were interviewed and examined by trained professionals to assess any oral mucosal changes. Results: Oral mucosal lesions were found in 322 (26.8%) subjects who had tobacco smoking and chewing habits as compared to 34 (2.8%) subjects without those habits. Oral leukoplakia (8.2%) and oral submucous fibrosis (OSF) (7.1%) were the prevalent oral mucosal lesions found in subjects who had those habits, while the other lesions (1.7%) namely; oral candidiasis, median rhomboid glossitis, recurrent apthous ulcer, frictional keratosis, and oral lichen planus (0.9%) were frequently reported among individuals without those habits. The odds of developing oral lesions in subjects with tobacco habits was nearly 11.92 times that of abstainers (odds ratio, OR = 11.92, 95% confidence intervals, CI = 10.61-14.59%). Conclusion: The study showed that the risk of the development of oral lesions associated with tobacco smoking, chewing, or both is quite high. Males who had one or more of these habits showed more frequent oral changes than females. The study reinforces the association of OSF with gutkha and areca nut chewing, and leukoplakia, erythroplakia, and oral cancer with tobacco smoking, chewing, or mixed habits.